Effect of Indian Camphorweed (Pluchea indica) Leaves Ethanol Extract on rd3 Instar Larva Spodoptera litura Mortality - Bahri, Syamsul; Mertha, I Wayan; Khairuddin, Khairuddin (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Spodoptera litura, known as the tobacco cutworm or oriental leafworm moth, is a highly destructive, polyphagous pest that attacks over 250 crops, causing significant damage to leaves and making it a serious threat across Asia, Oceania, and Africa. To control the population of this species, the use of insecticides of plant origin is worth considering. Pluchea indica is a species known to contain secondary metabolites with insecticide properties. This study aimed to determine the effect of ethanol extract of indian camphorweed (Pluchea indica) leaves on rd3 instar larva Spodoptera litura mortality. This study used a completely randomized design (CRD) consisting of 6 concentrations of indian camphorweed (Pluchea indica) leaves ethanol extract, namely, 0, 250, 300, 350, 400, 450 and 500 ppm. Each treatment used 7 larvae with 5 repetitions. The mortality of larvae was observed for a 24-hour period by counting the number of nd2 instar larvae that died after having been treated. All data collected were analyzed with One-Way ANOVA. Statistical analysis showed that the ethanol extract of beluntas leaves significantly increases the nd2 instar larvae of S. litura mortality by 60.0% at a concentration of 500 ppm.